A Numerical Study on the Melt Track in Selective Laser Melting Using Aluminium Alloy 6061 - Sing, S. L. (2016)
Selective laser melting (SLM) is a type of additive manufacturing (AM), rapid prototyping or 3D printing method that is capable of building complex metallic structures. In this paper, the relationships of process parameters such as laser power and scan speed with the melt penetration, melt width, mass of material melted and evaporated are established based on a validated FE model on SLM that considers powder-to-solid transition, volume shrinkage and evaporation.